Community Colleges, Human Capital, and Economic Growth in Developing Countries. Issue 177 (March 2017) - Tyndorf, Darryl M.; Glass, Chris R.
Abstract : This chapter argues that increasing human capital through a combination of university and community college education promotes greater economic growth in developing countries.